Analysis of Marketed Surplus and Disposal Pattern of Milk in Ballia district of Uttar Pradesh - singh, priyanka (Indian Journal of Dairy Science, 2018)
The present study was conducted in 2016 in order to analyse the marketed surplus of milk and factors affecting it as well as disposal pattern of the milk. The study revealed that the out of overall average production which was 25.64 litre per day per household only 4.41 litre of milk was consumed per household per day and the remaining milk was disposed off. Thus the marketed surplus was 21.5 litre per day per household which was 83.85 percent of total milk produced. It was also found that among different factors affecting marketed surplus price had the highest and significant effect followed by milk production. Then finally the disposal pattern of milk shows that the major portion of milk (90.42 percent) had been marketed through unorganized channel and only 9.58 percent of milk was disposed off through dairy cooperatives. This shows the dominance of unorganized milk markets in the study area.